1999
DOI: 10.1001/archinte.159.21.2553
|View full text |Cite
|
Sign up to set email alerts
|

Patient Risk Factors for Adverse Drug Events in Hospitalized Patients

Abstract: Background: Adverse drug events (ADEs) are common in hospitalized patients, but few empirical data are available regarding the strength of patient risk factors for ADEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
191
3
12

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 304 publications
(217 citation statements)
references
References 43 publications
11
191
3
12
Order By: Relevance
“…Studies have shown that age, gender, co morbidity, number of drugs, and length of hospital stay are significant risk factors for development of ADRs [36,[39][40][41][42][43][44]. Our study revealed polypharmacy and multiple disease state as the most prevalent predisposing factors in patients who developed ADRs.…”
Section: Discussionmentioning
confidence: 52%
“…Studies have shown that age, gender, co morbidity, number of drugs, and length of hospital stay are significant risk factors for development of ADRs [36,[39][40][41][42][43][44]. Our study revealed polypharmacy and multiple disease state as the most prevalent predisposing factors in patients who developed ADRs.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, inter-rater reliabilities ranged from poor to excellent (kappa 0.19-0.98; overall agreement 26-97%). Of the 24 (17%) articles that reported excellent reliability of the preventability assessment (kappa >0.81), one study used an explicit algorithm in the fourth group (36) and 23 used more implicit methods (8,9,22,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). In four (3%) articles, reliability assessments were mentioned, but as no exact figures for the reliability of the preventability assessment were presented, the articles are not presented in Table IV (24,57,58).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the United States, United Kingdom, and Australia indicate that errors or adverse events occur in the range of 1.1% to 16.6% of all hospital admissions, [3][4][5][6] with many showing a greater incidence with age, complexity, and acuity of the patient. 3,[7][8][9][10][11] Analysis of malpractice claims indicates that diagnostic error is both the leading cause of paid claims and the most costly category. 12,13 However connecting error types to actual error rates from audits, selfreports, and other databases without a known denominator is not possible.…”
Section: Diagnostic Error In Medicine and Critical Carementioning
confidence: 99%